Government Expenditure and Human Development in Indonesia - Suyanto, Suyanto; Suprijati, Jajuk; Budiarti, Wiwik; Ramdhan, Dendy Syahru; Almughni, Muhammad Afdha Alif; Muhtar, Muhtar; Junaedi, Junaedi; Standsyah, Rahmawati Erma; Mustofa, Amirul; Haryati, Eny (AKRUAL: Jurnal Akuntansi, 2025)
Backgrounds: Indonesia experiences economic and human resource inequality. This inequality is caused by several factors, one of which is development that focuses on the island of Java. Apart from that, the Indonesian government has designated 62 disadvantaged areas, all of which are outside the island of Java. Objectives: This research aims to examine and analyze the direct and indirect influence of capital expenditure and operational expenditure on human development in underdeveloped regions in Indonesia through the regional economy as an intervening variable. Therefore, this research focuses on underdeveloped areas in Indonesia from 2011 to 2021. Method: This research is quantitative using the panel regression method with path analysis. The variables used in this research are government spending as an exogenous variable, and human development as an endogenous variable. Results: The results of this research show that capital expenditure has a negative effect on human development, while operational and regional economic expenditure has a positive effect on human development in underdeveloped areas. On the other hand, operational spending has a positive effect on the regional economy, but capital spending has a negative effect on the regional economy of underdeveloped regions. Capital expenditure has a negative impact on the regional economy because government spending so far has not met the needs of regional communities, and its value is still relatively low, inefficiency, and development is still focused on urban areas on the island of Java, so there is a need for more inclusive infrastructure investment.